2005
DOI: 10.1108/02640470510603697
|View full text |Cite
|
Sign up to set email alerts
|

The use of information technology (IT) by electronic media workers in Delta State, Nigeria

Abstract: PurposeTo find out the patterns of information technology (IT) use by electronic media workers in Delta State, Nigeria.Design/methodology/approachThe survey design using questionnaires to collect data is employed.FindingsThese reveal the personal characteristics of the respondents – their sex, age, qualification, ranks/job titles, name of media organization; that all the respondents use IT facilities/components; most of them use computers system daily; a majority do not use internet/e‐mail nor fax machine but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Internet could take up to 5 min or more to open a particular web page. Power outages are problems militating against information/Internet provision and use in African countries (Adomi et al, 2003;Adomi et al, 2005;Adomi, 2010). Finally, the findings revealed that majority of the postgraduate students suggested that the major strategies to overcoming the likely problems are; adequate Internet services, adequate power supply, free access to sites and subsidized charges.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Internet could take up to 5 min or more to open a particular web page. Power outages are problems militating against information/Internet provision and use in African countries (Adomi et al, 2003;Adomi et al, 2005;Adomi, 2010). Finally, the findings revealed that majority of the postgraduate students suggested that the major strategies to overcoming the likely problems are; adequate Internet services, adequate power supply, free access to sites and subsidized charges.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Spacey et al (2003) suggested that training is an appropriate means of enabling staff to cope effectively with technological change and that, since staff have different needs, it is best to offer a range of training methods. Adomi et al (2005) found that all the respondents in a survey in Nigeria use IT components and most of them use computer system daily, but frequent power outages, among other factors, militate against use of the use of ICT. Adeyoyin (2005), also in Nigeria, found that out of about 268 professional librarians, only 87 (32.46 per cent) were ICT-literate, and of the 358 paraprofessionals only 7.8 per cent were ICT-literate, and of the 1,133 'other' staff members 6 per cent staff were ICT-literate.…”
Section: Library Automationmentioning
confidence: 99%